2010
DOI: 10.1016/j.jebo.2010.02.013
|View full text |Cite
|
Sign up to set email alerts
|

The good, the bad, and the talented: Entrepreneurial talent and selfish behavior

Abstract: Abstract:Talent allocation models assume that entrepreneurially talented people are selfish and thus allocate into unproductive or even destructive activities if these offer the highest private returns. This paper experimentally analyzes selfish preferences of the entrepreneurially talented. We find that making a distinction between creative talent and business talent explains systematic differences in selfish behavior. Generally, both the less business talented and the more creative are more willing to forego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 56 publications
2
45
0
Order By: Relevance
“…While aggressive behavior in competitions is already associated with entrepreneurs (e.g., Utsch et al 1999;Hmieleski and Lerner 2016), such behavioral tendencies within competitive environments are distinct from preferences to enter competitions. 5 Relatedly, individuals maximizing own rewards relative to others' rewards are also considered to be competitive individuals (e.g., van Lange et al 1997;Fehr and Schmidt 1999) and these distributional preferences are linked to selection into entrepreneurship (e.g., Weitzel et al 2010). While significant correlations between such distributional preferences and individual competitiveness are reported (Bartling et al 2009), distributional preferences also differ from our conceptualization of individual competitiveness, because they relate to behavior in contexts where individuals' rewards are mutually dependent on one another, that is, to behavior in competitive environments, but not to preferences to select into such environments.…”
Section: Individual Competitivenessmentioning
confidence: 99%
“…While aggressive behavior in competitions is already associated with entrepreneurs (e.g., Utsch et al 1999;Hmieleski and Lerner 2016), such behavioral tendencies within competitive environments are distinct from preferences to enter competitions. 5 Relatedly, individuals maximizing own rewards relative to others' rewards are also considered to be competitive individuals (e.g., van Lange et al 1997;Fehr and Schmidt 1999) and these distributional preferences are linked to selection into entrepreneurship (e.g., Weitzel et al 2010). While significant correlations between such distributional preferences and individual competitiveness are reported (Bartling et al 2009), distributional preferences also differ from our conceptualization of individual competitiveness, because they relate to behavior in contexts where individuals' rewards are mutually dependent on one another, that is, to behavior in competitive environments, but not to preferences to select into such environments.…”
Section: Individual Competitivenessmentioning
confidence: 99%
“…However, across studies that rely on a common taxonomy for personality traits, namely the widely accepted five-factor model of personality (e.g., McCrae & Costa, 1999), the empirical picture has turned out somewhat inconsistent: Not one of the classical five factors was a consistent predictor of DG altruism and the modal finding for each factor across studies is actually a null-effect. Even Agreeableness -which is commonly considered the one factor out of the five-factor model that should positively predict altruistic behavior (Denissen & Penke, 2008;Ferguson et al, 2011) -could only be shown to positively predict DG altruism in some studies (e.g., Baumert, Schlösser, & Schmitt, 2014;Becker, Deckers, Falk, & Kosse, 2012;Ben-Ner, Kramer, & Levy, 2008) but not (or even negatively) in others (e.g., Ben-Ner & Kramer, 2011;Visser & Roelofs, 2011;Weitzel, Urbig, Desai, Sanders, & Acs, 2010). Of course, variation in study designs and methodological details may account for such inconsistencies, rather than the trait conceptualizations per se.…”
Section: Introductionmentioning
confidence: 99%
“…One plausible way for an entrepreneur to destroy inputs is through gaining political power and therefore influencing institutions (Desai et al 2013). Ever recently, in line with our interest, there has been a growing interest in explaining and investigating the allocation of entrepreneurship (Bowen and De Clercq 2008;Sobel 2008;Weitzel et al 2010). However, many have concentrated on the differentiation between productive and unproductive entrepreneurship and neglect the destructive one, with exceptions such as, e.g., Desai et al (2013), who propose a theoretical model on destructive entrepreneurship.…”
mentioning
confidence: 99%